Synthesis, antimycobacterial and antifungal evaluation of 3-arylaminopyrazine-2,5-dicarbonitriles - Palek, Lukás; Dvorák, Jaroslav; Svobodová, Michaela; Buchta, Vladimír; Jampílek, Josef; Dolezal, Martin (Archiv der Pharmazie, 2008)
This paper describes preparation and biological evaluation of pyrazinamide analogues. Pyrazinamide with its simple structure gives a good opportunity for further modification regarding an increase of its antimycobacterial activity. We prepared a series of compounds derived from pyrazine-2,5-dicarbonitrile with arylamino substitution in position 3. All compounds were assayed in vitro against major Mycobacterium and various Fungi species. The best activity was found in 3-{[3-(trifluoromethyl)phenyl]amino}pyrazine-2,5-dicarbonitrile 11 with the value of 6.25 micromol(-1) against M. tuberculosis H(37)Rv and moderate activity against minor Mycobacterium pathogens.
Keywords: Absidia; pyraziny; vztahy mezi strukturou a aktivitou; antituberkulotika; Structure-Activity Relationship; Mycobacterium; Microbial Sensitivity Tests; Antitubercular Agents; mikrobiální testy citlivosti; Nitriles; Aspergillus fumigatus; Antifungal Agents; Pyrazinamide; pyrazinamid; Candida; Chromatography, High Pressure Liquid; antifungální látky; vysokoúčinná kapalinová chromatografie; nitrily; Pyrazines; Trichosporon